Personality Intolerance of Ambiguity in Planning and Developing Bumdes Behavior - Siallagan, Hamonangan; Sinurat, Mangasa; Gaol , Vebry Lumban; Sinaga , Pebrien Mauli (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine the influence of psychological factors on the behaviour of planning and developing illage-owned enterprises (BUMDes) with the aim of increasing village original income (PADesa). The factors studied include belief in the usefulness of BUMDes, attitude, subjective norm, perceived behavioural control, interest, as well as the moderating role of ambiguity ntolerance. Primary data was collected through questionnaires distributed to respondents, and data analysis was conducted using the structural equation modelling (SEM) approach using the partial least squares (PLS) technique through WarpPLS software. The results showed that all hypotheses proposed were supported, with a negative influence from intolerance of ambiguity. The implication of this study is that cognitive theory, along with the Theory of Planned Behaviour (TPB), can be used to understand and explain the behaviour of planning and developing BUMDes so as to increase village original revenue.